Kindle Fire HDX for dummies - Muir, Nancy (John Wiley & Sons, Inc., 2014)
The Kindle Fire HDX is Amazon's premiere tablet. With its new,more powerful Android operating system, this latest version hassome exciting bells and whistles along with the features that havemade the Fire a tablet fan favorite: access to the amazing AmazonAppstore, online music storage, a large music and video store, ahuge e-book library, and easy one-step ordering from Amazon. Thisfull-color, For Dummies guide shows you how to takeadvantage of all the Kindle Fire’s functionality includingbrowsing the web, sharing photos, watching videos, playing games,downloading apps, reading newspapers and magazines, andpersonalizing the device for your needs